The Waste Management with Reward System Project Proposal: A Case Study of Bushenyi-Ishaka Monicipality in Uganda. - Turihabwe, Christopher; Ninsiima, Ivan (Kabale University, 2024)
This research work generally summarizes the activities carried out in the design and implementation of the Waste Management with a rewards system. Waste management is the process of collecting, transporting, processing, recycling, and disposing of waste materials like empty bottles, and polythene bags, in a way that minimizes the negative impact on human health and the environment. Waste Management with a Reward System encourages waste-producer communities to engage in recycling activities and make use of different junkshops and recycling centers. The system allows members to register and conveniently search for junk shops and recycling centers to dispose of their recyclable waste materials. The System further allows electronic record keeping of garbage collection reports as a basis for giving rewards to active members who participate in recycling activities. These objectives are creating waste management with rewards, creating login and register pages, Admin accounts, junkshop, and recycling centers. The project’s design is constructed to visualize the attainment of these aims using Unified Modeling Language diagrams, Entity Relationship diagrams, as well as Data Flow Diagrams. In the implementation part of this project, the methodology will be used for the development of this project. Also, Visual Studio Professional 2010 will be used as an Integrated Development Environment (IDE), developed using PHP programming language. Requirements will be tested to the best of their ability using the following format of the Institute of Electrical and Electronics Engineers (IEEE).